Thinking-for-speaking patterns in the L2 classroom: A mindful conceptual engagement approach to teaching motion events - Aguiló-Mora, Francisca; Negueruela-Azarola, Eduardo (Frontiers in Communication, 2022)
Inspired by sociocultural psychology principles applied to understanding language learning and conceptual development, this participatory action research illustrates a pedagogical intervention to teach motion events as conceptual categories in the Second Language (L2) classroom. The goal is to develop and implement conceptual engagement tasks that promote mindful understanding, application, and internalization of motion events as productive concepts in communicative tasks. This is the basis for a Mindful Conceptual Engagement (MCE) approach to L2 development. We focus on L2 Spanish classroom learners when asking-and-giving-directions. This task is conceptually challenging for First Language (L1) English L2 Spanish learners because it is connected to motion events and how Thinking-for-Speaking (TFS) patterns operate in L2 communication. Twenty-three L2-Spanish students from three different courses participated in the project. A selection of coded data and examples of graphic representations are analyzed. Findings illustrate how to teach motion events conceptually and how MCE promotes conceptual awareness and control of L2 communicative features. We also document the challenges of developing functional conceptual categories of meaning as they only emerge when mindfully applied in conceptual engagement tasks. L2 learners must create their own conceptual representations as learning tools to understand motion events. It is concluded that shifting L1 TFS patterns requires creative and mindful conceptual engagement by L2 learners.